2020
DOI: 10.21273/horttech04689-20
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Sweetpotato Varieties Grown Using Black Plastic Mulch in Pennsylvania

Abstract: Sweetpotato (Ipomoea batatas) production in Pennsylvania and the northeastern United States has been increasing steadily. The performance of eight commercially available sweetpotato varieties and two unreleased accessions grown on raised beds and covered with black plastic mulch in Pennsylvania was evaluated. All varieties and accessions were evaluated in 2 successive years (2018 and 2019) at Rock Springs, PA. There were statistically significant differences in total marketable yield (TMY), but not in all yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Yet, sweetpotato can grow in heavy soils, but yield and quality can decrease. However, recent studies have shown potential in adapting sweetpotato management and production strategies in less-than-ideal scenarios [2,[11][12][13][14]. Considering that, the adaptability and adoptability of sweetpotato in the northern latitudes (e.g., Canada, Mid-Atlantic, and Northeast U.S.) has been wellresearched [2,[11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Yet, sweetpotato can grow in heavy soils, but yield and quality can decrease. However, recent studies have shown potential in adapting sweetpotato management and production strategies in less-than-ideal scenarios [2,[11][12][13][14]. Considering that, the adaptability and adoptability of sweetpotato in the northern latitudes (e.g., Canada, Mid-Atlantic, and Northeast U.S.) has been wellresearched [2,[11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this is the first study that evaluates the production of Petite sweetpotato separate from other sweetpotato standards for grades of sweetpotato using different varieties in the Mid-Atlantic and Northeastern U.S. region. The U.S. population has steadily increased its consumption of fresh market sweetpotato, but sweetpotato is also progressively being used for high-value alternate markets, such as processed foods (e.g., French fries and chips) and industrial products (starch, flour, food dyes), among others [2]. Typically, direct-market sales through local farmers' markets and grocery stores are the principal outlet for vegetable farmers, and locally grown sweetpotatoes throughout the Mid-Atlantic and Northeastern U.S. [2].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations